Epistemologi Observasi Qur'ani: Integrasi Dimensi Empiris dan Spiritual dalam QS. Al-Ghashiyah Ayat 17–2 - Afrizal El Adzim Syahputra; Mochammad Rizal Fanani; Muhammad Rizal Rifa'i (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to examine the epistemology of Qur’anic observation in Surah Al-Ghashiyah verses 17–20 by exploring the integration of empirical and spiritual dimensions as the foundation of knowledge from the Qur’anic perspective. The study is motivated by the persistent dichotomy between empirical rationality and spirituality in modern scholarship, while studies on the epistemological structure of observation in the Qur’an remain limited. Employing a qualitative library research design, this study applies the thematic (tafsīr maudhū‘ī) approach. The primary data consist of Surah Al-Ghashiyah verses 17–20, analyzed through classical and contemporary Qur’anic commentaries and supported by literature on Islamic epistemology and integrative education. The findings reveal that the Qur’an constructs an epistemology of observation through the sequential contemplation of the camel, the sky, the mountains, and the earth, guiding human beings from empirical reality toward transcendental awareness. In the Qur’anic perspective, observation extends beyond sensory perception through the integrated processes of naẓar (observation), tafakkur (critical reflection), and tadabbur (contemplative understanding), which harmonize the senses, reason, and the heart in the acquisition of knowledge. This epistemological framework unites empirical facts with spiritual values, producing knowledge that is not merely informative but also transformative. The study contributes to strengthening the paradigm of Qur’anic epistemology as a conceptual foundation for the development of integrative Islamic education capable of addressing contemporary intellectual challenges.